Respuesta :
If you plug in the second equation (x=5-3/2y) into the first, you get:
5(5-3/2y) - 4y = 7
Simplify:
25 - 15/2y - 4y = 7
-15/2 y - 8/2 y = 7-25
23/2 y = 18
y = 18 * 2/23 = 36/23
answer B!
5(5-3/2y) - 4y = 7
Simplify:
25 - 15/2y - 4y = 7
-15/2 y - 8/2 y = 7-25
23/2 y = 18
y = 18 * 2/23 = 36/23
answer B!
5(5-3/2y) - 4y = 7
Simplify:
25 - 15/2y - 4y = 7
-15/2 y - 8/2 y = 7-25
23/2 y = 18
y = 18 * 2/23 = 36/23
Simplify:
25 - 15/2y - 4y = 7
-15/2 y - 8/2 y = 7-25
23/2 y = 18
y = 18 * 2/23 = 36/23